Social Media Branding Pada Produk UMKM Bumay Kacbaw Jaya Sebagai Upaya Sosialisasi Pemasaran Digital Bagi Pelaku Usaha Mikro Kecil Dan Menengah (UMKM) - Ani Setiowati (BADAN PENERBIT STIEPARI PRESS, 2023)
Micro, Small and Medium Enterprises (MSMEs) play a crucial role in developing and advancing the national economy. One step that can be taken to improve MSME marketing is through implementing a digital marketing strategy. UMKM Bumay Kacbaw Jaya, which is located on Jl. Kalikepiting Jaya IX No.8, Surabaya, East Java, is currently not using e-commerce as a marketing medium for its products due to limited resources in managing social media and digital platforms. As a result of the internship activities, various initiatives have been taken, such as creating product mockup designs, catalog photos, TikTok content, creating e-commerce accounts, and holding digital marketing seminars at Kaza Mall, Surabaya, East Java, which were attended by several MSMEs in Surabaya . The aim of this journal is to analyze the role and urgency of social media branding in efforts to socialize digital marketing for MSMEs. Digital marketing through social media platforms is now a very effective tool for MSMEs to increase exposure, develop their brand and attract new customers. In this research, we applied a qualitative approach by conducting in-depth interviews with 10 MSME owners who have adopted social media branding in their marketing strategy. In its conclusion, this research emphasizes the importance of social media branding as an effective digital marketing strategy for Bumay Kacbaw Jaya MSMEs. Social media branding helps MSMEs increase their exposure and competitiveness in an increasingly competitive market. Therefore, we recommend that MSMEs consider the use of social media branding as a key element in their marketing strategy. This needs to be done by paying attention to relevant and interesting content, as well as maintaining consistent management. With the right adoption, social media branding can become a valuable resource for MSMEs to overcome challenges and take advantage of opportunities in this digital era.